Efficacy of neoadjuvant hyperthermic intraperitoneal chemotherapy in advanced high-grade serous ovarian cancer (the NHIPEC trial): study protocol for a randomised controlled trial - Hui Zhou; Jing Li; Qing Chen; Ji-Bin Li; Li-juan Wang; Yan-Fang Ye; Miao-Fang Wu; Chang-Hao Liu; Huai-Wu Lu; Ting-Ting Yao; Bing-Zhong Zhang; Yong-Pai Peng; et al. (BMJ Open)
Background Neoadjuvant chemotherapy (NACT) is an important treatment option for patients with ovarian cancer. Although intravenous NACT can improve optimal resection rates and decrease surgical morbidity and mortality, these advantages do not translate into a survival benefit. Ovarian carcinoma is mainly confined to the peritoneal cavity, which makes it a potential target for hyperthermic intraperitoneal chemotherapy (HIPEC). Our previous study showed that HIPEC could be used in the neoadjuvant setting, which was named neoadjuvant HIPEC (NHIPEC). Since hyperthermia is an excellent chemosensitiser, we hypothesised that the combination of NHIPEC and intravenous NACT could show superior efficacy to intravenous NACT alone.Methods This study is a single-centre, open-label, randomised (1:1 allocation ratio) phase 2 trial. A total of 80 patients will be randomly assigned into an experimental group (NHIPEC+intravenous NACT) or a control group (intravenous NACT). Patients in the experimental group will receive NHIPEC following laparoscopic evaluation, and four tubes will be placed via the laparoscopic ports, which will be used to administer NHIPEC. Then, perfusion with docetaxel (60–75 mg/m2) will be performed (43°C for 60 min, Day 0) followed by cisplatin (75 mg/m2, Day 1) infusion (43°C for 60 min) 24 hours later. After NHIPEC, two cycles of intravenous NACT will be given. Patients in the control group will receive three cycles of intravenous NACT. The primary endpoint is the proportion of patients who achieve a Chemotherapy Response Score (CRS) of 3 according to the CRS system. The secondary endpoints include progression-free survival, overall survival and the rates of complete resection and NHIPEC-related adverse events.Ethics approval and dissemination This study was approved by the Ethics Committee of Sun Yat-sen Memorial Hospital (approval number: 2020-ky-050). Results will be submitted to peer-reviewed journals and presented at national and international conferences.Trial registration number ChiCTR2000038173.